HERMENEUTIKA TAUHID: INTERPRETASI AMINA WADUD TERHADAP GENDER - Mohammad Fauzan Ni’ami; Moh. Irfan (Institut Ilmu Keislaman Zainul Hasan Genggong, 2023)
The research on this figure is motivated by the response of female feminists to the traditional model of text interpretation. The implication is that around the 19-20th centuries, figures appeared who sharply criticized the method of interpretation of the Qur’an in relation to women's texts, and criticized classical fiqh formulations which were considered discriminatory against women. The reason for choosing Wadud was because she was considered capable of reconstructing a gender-based interpretation of the Qur’an. The uniqueness of Wadud's methodological model of interpretation of the Koran is that the model of re-reading the Qur’an is based on women's experiences and without involving stereotypes that become the framework for men's interpretation. This article tries to look at the hermeneutic model offered by Amina Wadud comprehensively. By using this type of character study research and a gender approach, we reveal Wadud's discourse on gender and the interpretation model initiated to interpret the text of the Koran or hadith. The result is that Wadud offers a holistic-accommodative interpretation model. Thus, Wadud began to seek reformulation of the interpretation methodology that was relevant to the spirit of the universality of the Qur'an. Wadud presents a critical interpretation, namely hermeneutics of monotheism by emphasizing the significance of the prior text in the verses of the Qur'an. This is evidenced by the modification of Amina Wadud's text interpretation.